Riverine nitrogen and phosphorus output in an arid watershed: combined effects of anthropogenic nutrient inputs, land use, and hydrology - Min Cao; Wei Gao; Yuan Zhang; Fen Guo (Environmental Systems Research)
Abstract Riverine nitrogen export (RNE) and riverine phosphorus export (RPE) are the cumulative results of regional anthropogenic nitrogen and phosphorus inputs combined with land use and hydrological changes that primarily drive the eutrophication of downstream water bodies. This study focuses on the characteristics of high nitrogen and phosphorus concentrations as well as low discharge in rivers in arid regions, using the Liao River in northern China as an example. The spatiotemporal patterns of net anthropogenic nitrogen input (NANI) and net anthropogenic phosphorus input (NAPI) in the Liao River Basin during 2010 to 2020 were investigated. Results indicated that the multi-year averages for NANI and NAPI were 9453 kg N km−2 yr−1 and 1916 kg P km−2 yr−1, respectively. Our predictive models constructed based on the aforementioned influencing factors, explained 67% and 75% of the variations in RNE and RPE, respectively. Unlike previous studies, only a small portion of NANI and NAPI was exported through rivers. The RNE and RPE were 37 kg N km−2·yr−1 and 2 kg P km−2·yr−1, accounting for 0.42% of NANI and 0.12% of NAPI. RNE and RPE were significantly influenced by discharge and precipitation. The cropland ratio influenced the output ratio of NANI, whereas RPE was mainly influenced by the NAPI of developed land.